Анализ низших частот консольного анизотропного параллелепипеда в трехмерной постановке - Беспалова, Е.И.; Урусова, Г.П. (Прикладная механика, 2014)
Розроблено підхід для визначення нижчих частот пружного паралелепіпеда в 3-D постановці з врахуванням анізотропії матеріалу. Підхід базується на поєднанні метода оберненої ітерації і узагальненого методу Канторовича – Власова. Порівняння з результатами, отриманими методом скінчених елементів і методом Рітца, підтвердили правомірність запропонованої методики. Проведено аналіз впливу властивостей анізотропних матеріалів на нижчі частоти консольного паралелепіпеда. Показано, що для цього типу граничних умов зміна частот паралелепіпеда відповідає зміні домінуючих жорсткістних характеристик. An approach is developed to calculate the lower frequencies of an elastic parallelepiped within the 3D statement with allowance for material anisotropy. This approach is based on combination of the inverse method and Kantorovich-Vlasov method. A comparison with results obtained by the method of finite elements and the Ritz method certified of legitimacy of the technique proposed. An effect of properties of anisotropic materials on the lower frequencies of the consol parallelepiped is analyzed. It is shown that for this type of boundary conditions the change of frequencies of parallelepiped corresponds to the change of predominate stiffness characteristics